2011
DOI: 10.1007/s10620-011-1589-y
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Proton Pump Inhibitor Use and Anemia: A Retrospective Cohort Study

Abstract: Among adult patients receiving chronic PPI therapy, there is a significant decrease in hematologic indices from baseline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
82
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(87 citation statements)
references
References 18 publications
1
82
1
3
Order By: Relevance
“…High levels of consumption of coffee and tea and the excessive use of medications to inhibit stomach acid secretion may interfere with iron absorption. 19,20 While studies examining IDA in military personnel are limited, these findings are consistent with a recent study of iron status, ID and IDA prevalence among military personnel deployed to Afghanistan that found ID in 1 percent and 6 percent and IDA in 0 percent and 2 percent of males and females, respectively. 11 This report shows that 18 percent of females and 10 percent of males diagnosed with IDA experience a recurrence (i.e., recurrent or chronic) of their condition.…”
Section: E D I T O R I a L C O M M E N Tsupporting
confidence: 84%
“…High levels of consumption of coffee and tea and the excessive use of medications to inhibit stomach acid secretion may interfere with iron absorption. 19,20 While studies examining IDA in military personnel are limited, these findings are consistent with a recent study of iron status, ID and IDA prevalence among military personnel deployed to Afghanistan that found ID in 1 percent and 6 percent and IDA in 0 percent and 2 percent of males and females, respectively. 11 This report shows that 18 percent of females and 10 percent of males diagnosed with IDA experience a recurrence (i.e., recurrent or chronic) of their condition.…”
Section: E D I T O R I a L C O M M E N Tsupporting
confidence: 84%
“…One report describes that PPI use increased the length of intervals between bloodletting in patients with hemochromatosis (10). Sarzynski et al also retrospectively studied 98 patients who had started using PPIs and found that the hemoglobin (Hb) level had decreased in many of the patients one year later (11). A subgroup analysis was performed in that study, and possible correlations were examined between a decreased Hb level and various patient attributes, such as Helicobacter pylori infection, oral antiplatelet drug use and past medical history; however, no items correlating with a decreased Hb level were found.…”
Section: Discussionmentioning
confidence: 99%
“…Long-lasting PPI treatment is considered to increase risk for hip, wrist, and spine fractures, although there are no unanimously agreed pathophysiological mechanisms [8]. Treatment-induced acid suppression is connected with decreased absorption of iron and vitamin B, with consequent occurrence of anaemia [9,10]. Meta-analyses on a large scale population reported on escalation of community-acquired pneumonia in a population treated with PPI [11].…”
Section: Introductionmentioning
confidence: 99%